ANALISIS DAMPAK IMPLEMENTASI STANDAR PELAYANAN MINIMAL RUMAH SAKIT TERHADAP KINERJA KEUANGAN (STUDI PADA RSUD DR. H. MOH. ANWAR SUMENEP) - Anis Sufiati; - Prasetyono; F. A. Kurniawan (Universitas Trunojoyo Madura, 2013)
The objective of this study is to investigate the effect of implementation of minimum standards of service at Local Government Hospital of Sumenep District on financial performance. This is a qualitative research based on case study. Data used in this study was financial reports of year 2010 until 2012 and Performance Accountability Report of Government Institutions of year 2012 as a secondary data. In order to gather primary data, observation and interview have done on the staffs of Local Government Hospital of Sumenep District. The data is analyzed by Pattern-Matching. This study found that Local Government Hospital of Dr. H. Moh. Anwar Sumenep District, has implement the Minimum Standards of Service based on the Decision of the Minister of Health No. 129/Menkes/SK/II/2008, however it has not been entirely implemented. This implementation has increased the financial performance of the hospital significantly since 2010 until 2012. The cost recovery in 2010 was 45%, in 2011 was 54%, and in 2012 was 69%. Moreover, the income realization of this hospital in 2012 has also passed the target.